Effect of the Interfacial Transition Zone on Basic Mechanical Properties of a Solid Composite Propellant - Shen, L.L.; Shen, Z.B.; Cui, H.R.; Li, H.Y.; Zhi, S.J. (Проблемы прочности, 2018)
The evaluation of basic mechanical properties are shown to be of importance for the solid composite propellant development and application. The numerical analysis approach termed the three-phase Voronoi cell finite element method, was proposed to evaluate of the interfacial transition zone effect. Numerical results showed that the performance of the effective modulus could be essentially enhanced by increasing the zone thickness. The module of the composite with the inhomogeneous zone was higher than that of the composite with the homogeneous one. The effect of different zones on volume fractions and matrix moduli was also calculated. The Voronoi method can also be helpful for analyzing the characteristic properties of other three-phase composites.